The impact of the origin of surgical sperm retrieval on placental and embryonic development: The Rotterdam Periconception cohort - Hoek, Jeffrey (Andrology, 2020)
BACKGROUND: In patients with azoospermia, pregnancy can be achieved after surgical techniques using sperm retrieved from the testis or epididymis, which can impact on DNA integrity and epigenetics. DNA of the fetus and placenta is equally derived from both parents; however, genes important for placental development are expressed from the paternal alleles. Therefore, the origin of sperm may affect fetal and placental development. OBJECTIVES: To investigate whether first‐trimester trajectories of embryonic and placental development of pregnancies conceived after intracytoplasmic sperm injection (ICSI) with testicular sperm extraction (TESE) or microsurgical epididymal sperm aspiration (MESA), are different from pregnancies after ICSI with ejaculated sperm or natural conceptions. MATERIALS AND METHODS: A total of 147 singleton ICSI pregnancies, including pregnancies conceived after TESE (n = 23), MESA (n = 25) and ejaculated sperm (n = 99), and 380 naturally conceived and 140 after IVF treatment without ICSI were selected from the prospective Rotterdam periconception cohort. Crown‐rump length (CRL), embryonic volume (EV), Carnegie stages, and placental volume (PV) at 7, 9, and 11 weeks of gestation were measured using 3D ultrasound and virtual reality technology. RESULTS: Linear mixed model analysis showed no differences in trajectories of CRL, EV, and Carnegie stages between pregnancies conceived after ICSI with testicular, epididymal, and ejaculated sperm. A significantly positive association was demonstrated for PV between pregnancies conceived after TESE‐ICSI (adjusted beta: 0.28(95%CI: 0.05‐0.50)) versus ICSI with ejaculated sperm. Retransformation to original values showed that the PV of pregnancies after TESE‐ICSI is 14.6% (95%CI: 1.4%‐25.5%) larger at 11 weeks of gestation compared to ICSI pregnancies conceived with ejaculated sperm. DISCUSSION AND CONCLUSION: Here we demonstrate that the first‐trimester growth trajectory of the placenta is increased in pregnancies conceived after TESE‐ICSI compared to those conceived after ICSI with ejaculated sperm. Findings are discussed in the light of known differences in sperm DNA integrity, epigenetics, and placental gene expression.